Cybersecurity essentials - Brooks, Charles J.; Grow, Christopher; Craig, Philip (Engineer); Short, Donald (John Wiley & Sons Inc., 2018)
"Cybersecurity Essentials" provides a comprehensive introduction, with expert coverage of essential topics required for entry-level cybersecurity certificates. It covers the four distinct challenges of creating an effective cybersecurity defense: securing the infrastructure, securing devices, securing local networks, and securing the perimeter. The authors summarize the fundamental concepts of each challenge and include real-world scenarios that show how these vulnerabilities look in everyday computing. The text offers a summary of the key concepts, review questions, and hands-on exercises designed to help assess an understanding of key concepts. -- From publisher's description.